Comparison of clinical and pathological characteristics of isolated aortitis and Takayasu arteritis with ascending aorta involvement. Issue 4 (18th January 2012) - Wang, Hongyue; Li, Li; Wang, Linlin; Chang, Qian; Pu, Jielin
Abstract : Aims: Isolated aortitis (IA) is a newly recognized condition, but its differentiation from Takayasu arteritis (TA) is still a challenge. This study aims to explore the characteristics of IA. Methods: The clinical and pathological data of 965 cases with excised ascending aortas were obtained by chart and slide review. IA cases were compared with TA cases and examined for CD3, CD4, CD8, CD20, CD68, CD138 and IgG4 of the infiltrates using immunohistochemistry. Results: 24 cases of IA and eight cases of TA were identified. IA cases tended to be older than TA cases (mean 46.3 vs 33.9 years). Both groups had the same male/female ratio (1.0). IA cases tended to have a bigger aortic diameter (mean 59.7 vs 47.6 mm), statistically less intimal thickening (mean 678 vs 1101 μm), fewer lesions outside the ascending aorta (8% vs 100%), a lower erythrocyte sedimentation rate (mean 14.6 vs 27.0 mm/h) and more active aortitis (75.0% vs 62.5%) than TA cases. The number of CD3+ cells was equal to CD20+ cells in the media but fewer than CD20+ cells in the adventitia of IA cases. Their CD4/CD8+ ratio ranged from 1.0 to 1.8 while the number of CD68+ macrophages varied largely. IgG4+ cells ranged from 0 to 40 (mean 4) cells/HPF and the IgG4+/CD138+ ratio ranged from 0 to 0.36 (mean 0.06) in IA cases. Conclusions: Cases of IA tend to have more histologically active inflammation except for a relatively normal erythrocyte sedimentation rate, localised lesions and milder intimal fibrosis than cases of TA. IgG4 abnormality may not be the main cause of IA.